From antiferromagnetism to high- Tc weak ferromagnetism manipulated by atomic rearrangement in Ba3NiOs2 O9 - Feng, Hai L.; Chen, Jie; Hu, Zhiwei; Wang, Xiao; Reehuis, Manfred; Adler, Peter; Hoser, Andreas; Wu, Mei-Xia; Agrestini, Stefano; Vasili, Hari Babu; Herrero-Martin, J.; Nataf, Lucie; et al. (Physical Review Materials, 2020)
Polycrystalline samples of Ba3NiOs2O9 were synthesized at ambient pressure (AP) and high pressure (HP) conditions, respectively. Both samples are electrically semiconducting. The AP Ba3NiOs2O9 crystallizes in the 6H perovskite structure with space group P63/mmc, consisting of face-sharing Os2O9 dimer units and corner-sharing NiO6 octahedra. Magnetic measurements indicated that AP Ba3NiOs2O9 is antiferromagnetically ordered below 130 K. HP Ba3NiOs2O9 crystallizes in the 6H perovskite structure too, but the face-sharing octahedral sites appear to be occupied by both Ni2+ and Os5+ ions, whereas the corner-sharing site is occupied exclusively by Os5+. HP Ba3NiOs2O9 undergoes a high-temperature (≈400K) weak ferromagnetic transition, which is much different from the antiferromagnetism of the AP phase. The long-range magnetic order of HP Ba3NiOs2O9 was confirmed by neutron powder diffraction. X-ray magnetic circular dichroism analysis supported ferromagnetic coupling between Os and Ni moments which leads to a spin arrangement, where the ferromagnetic moments mainly arise from Ni2+ ions.
CRIS-Team Scopus Importer:2022-04-14